2017
DOI: 10.4172/2471-2728.1000179
|View full text |Cite
|
Sign up to set email alerts
|

Study on Supplying Boron to Coffee on Basaltic Soil in Central Highlands of Vietnam

Abstract: Coffee trees have high nutrient requirements, including boron (B). A field experiment with 2 factors of applying methods (leaf and root) and doses (0, 1, 2 and 3 kgs B ha -1 yr -1 ) was implemented on basaltic soil in Central Highlands of Vietnam during 2015-2016. The results showed that supplying B remained appropriate B content in leaves, reduced in curly leaves and dropped fruits and increased in coffee productivity by 2.3-10.2% in comparison with control. The treatments of supplying 3 kg ha -1 got highest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…In Arabica coffee in Brazil, Santinato et al [59] found that the application of B at a rate higher than 2.0 kg.B.ha −1 linearly reduced the yield by 0.33 coffee bags.ha −1 (0.02 t of green coffee beans.ha −1 ) per kg of B applied in excess of 2.0 kg.B.ha −1 . In contrast Cong [67], working on a 10-year-old Robusta coffee plantation during one season in a highly acidic soil in Vietnam (basaltic soil of the Central Highlands), reported an average yield increase of 10.2% with the application of 3.0 kg B.ha −1 . These results indicate that the response to B nutrition is variable according to the coffee species and the environment.…”
Section: Influence Of B On Coffee Productivitymentioning
confidence: 98%
“…In Arabica coffee in Brazil, Santinato et al [59] found that the application of B at a rate higher than 2.0 kg.B.ha −1 linearly reduced the yield by 0.33 coffee bags.ha −1 (0.02 t of green coffee beans.ha −1 ) per kg of B applied in excess of 2.0 kg.B.ha −1 . In contrast Cong [67], working on a 10-year-old Robusta coffee plantation during one season in a highly acidic soil in Vietnam (basaltic soil of the Central Highlands), reported an average yield increase of 10.2% with the application of 3.0 kg B.ha −1 . These results indicate that the response to B nutrition is variable according to the coffee species and the environment.…”
Section: Influence Of B On Coffee Productivitymentioning
confidence: 98%
“…Secondly, shrink-tailed regression eliminates abnormal data in individual years that may bias global estimation results. All variables in the model undergo 1% shrink-tailed treatment, and the resulting outcomes are displayed in model (8). Finally, the core explanatory variables are replaced, with carbon emissions resulting from fertilizers used as a proxy variable for FNSP [77,78].…”
Section: Endogeneity Treatment and Robustness Testmentioning
confidence: 99%
“…However, the effective utilization efficiency remains less than half that of developed countries [7]. Notably, fertilizer's marginal contribution rate is gradually declining [8]. Excessive fertilizer inputs not only escalate the economic costs of agricultural production [9] but also lead to severe fertilizer nonpoint source pollution (denoted as FNSP) [10,11], posing significant threats to food security and the sustainable development of agriculture [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…However, there is still controversy as to the best way to apply B to coffee trees. There are reports on better results both to soil and foliar fertilization, however, B leaf spraying results in better nutrient use efficiency (Cong, 2017). Furthermore, an increase in B leaf does not always result in higher yield (Marubayashi et al, 1994;Lima Filho and Malavolta, 1998;Fernandes et al, 2012), and this may be due to poor redistribution of the nutrient.…”
Section: Introductionmentioning
confidence: 99%